Microscale dynamics of electrophysiological markers of epilepsy. Issue 11 (November 2021) - Yang, Jimmy C.; Paulk, Angelique C.; Salami, Pariya; Lee, Sang Heon; Ganji, Mehran; Soper, Daniel J.; Cleary, Daniel; Simon, Mirela; Maus, Douglas; Lee, Jong Woo; Nahed, Brian V.; Jones, Pamela S.; et al.
Highlights: PEDOT:PSS microelectrodes with 50 µm spatial resolution uniquely reveal spatiotemporal patterns of markers of epilepsy. High-resolution recording can track interictal discharges and reveal cortical domains involved in microseizures. High frequency oscillations detected by microelectrodes demonstrate localized clustering on the cortical surface. Abstract: Objective: Interictal discharges (IIDs) and high frequency oscillations (HFOs) are established neurophysiologic biomarkers of epilepsy, while microseizures are less well studied. We used custom poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) microelectrodes to better understand these markers' microscale spatial dynamics. Methods: Electrodes with spatial resolution down to 50 µm were used to record intraoperatively in 30 subjects. IIDs' degree of spread and spatiotemporal paths were generated by peak-tracking followed by clustering. Repeating HFO patterns were delineated by clustering similar time windows. Multi-unit activity (MUA) was analyzed in relation to IID and HFO timing. Results: We detected IIDs encompassing the entire array in 93% of subjects, while localized IIDs, observed across < 50% of channels, were seen in 53%. IIDs traveled along specific paths. HFOs appeared in small, repeated spatiotemporal patterns. Finally, we identified microseizure events that spanned 50–100 µm. HFOs covaried with MUA, but not with IIDs. Conclusions: Overall, these data suggest that irritable cortex micro-domains may form part of an underlying pathologic architecture which could contribute to the seizure network. Significance: These results, supporting the possibility that epileptogenic cortex comprises a mosaic of irritable domains, suggests that microscale approaches might be an important perspective in devising novel seizure control therapies.